An assessment of infrastructural development and enrollment in elementary education in Odisha - Majhi, Nimani and Mallick, Minati (Productivity)
Being an important component of the Human Development Index, education plays a very important role in the economic progress of an economy. The right to education has been enshrined as a fundamental right in the Constitution of India, which states that: (3z(Bthe State shall provide free and compulsory education to all children aged six to fourteen years in such a manner as the state may, by law, determine.(3y (BBoth the central and the state governments have been paying increased attention to the need to provide (3z(Beducation for all(3y(B. Sarva Shiksha Abhiyan (SSA) is one of the flagship programmes of Government of India, which has been implemented in all the 30 districts of Odisha since 2001 in order to achieve universal elementary education. Availability of physical infrastructure is crucial for ensuring quality in elementary education. In this back drop an attempt has been made in the present study to construct a physical infrastructure index for government and private schools across the districts of Odisha, while assessing the role this plays in improving the enrolment (using secondary data collected from the report of DISE for the year 2014-15).- Reproduced s